ENHANCING DIGITAL CONTENT DESIGN LITERACY THROUGH CANVA TRAINING FOR PARTICIPANTS IN THE 2026 PHASE 2 NATIONAL COMMUNITY SERVICE PROGRAM - Ferdinandus Lidang Witi; Yosep Thobias Parera; Maria Adelvin Londa (LPPM Universitas Flores, 2026)
Digital transformation demands that the younger generation develop the ability to create creative and communicative digital content. One important skill to develop is digital content design with the easily accessible, user-friendly Canva platform. The 2026 National Community Service Phase 2, themed